Higher oxidative balance score is associated with lower female infertility: a cross-sectional study - Lei, Xiong; Liu, Xiling; Yu, Chunchun; Xia, Lijing; Zhou, Liwen; Yao, Can; Xu, Zhixiao (Frontiers in Nutrition, 2024)
Background: An imbalance of the pro-oxidant and anti-oxidant profiles in the body contributes to the development of diseases, including female infertility.In this study, we performed a secondary analysis of the National Health and Nutrition Examination Survey and calculated the values of oxidative balance score (OBS). A weighted logistic regression model was used to explore the potential relationship between OBS (continuous factor and quartile set) and female infertility, and the P for trend was calculated. Subgroup analyses were also carried out further to explore the association between OBS and female infertility, and the P for interactions were obtained.Results: There were 1,626 females (aged 18 to 45) were included in the study, including 198 with infertility and a prevalence of approximately 13.28%. Multifactorial logistic regression showed a 5% decrease in infertility for each unit increased in OBS (OR, 0.95; 95% CI, 0.92 to 0.98). When OBS was used as a categorical variable, female infertility decreased by 60% in the highest OBS group compared with the lowest OBS group (OR, 0.40; 95%CI, 0.21 to 0.74). In addition, subgroup analyses showed that the negative association between OBS and infertility was significant in the nonchronic-disease (hypertension and diabetes) population, less than high school educational background, poverty to income ratio (1 to 3), and those more than 30 years of age.Higher OBS was negatively associated with female infertility. Further prospective studies are needed to determine causality and to provide new perspectives on female infertility in the context of diet and lifestyle.